A Disintegrating Rocky World Shrouded in Dust and Gas: Mid-infrared Observations of K2-22 b Using JWST - Nick Tusay; Jason T. Wright; Thomas G. Beatty; Steve Desch; Knicole Colón; Tushar Mittal; Hugh P. Osborn; Beatriz Campos Estrada; James E. Owen; Jessica Libby-Roberts; Arvind F. Gupta; Brad Foley; et al. (The Astrophysical Journal Letters, 2025)
The disintegrating ultrashort period rocky exoplanet K2-22 b periodically emits dusty clouds in a dynamically chaotic process resulting in a variable transit depth from 0% to 1.3%. The effluents that sublimate off the surface and condense out in space are probably representative of the formerly interior layers convectively transported to the molten surface. Transmission spectroscopy of these transiting clouds reveals spectral fingerprints of the interior composition of this rocky world. We used JWST’s Mid-Infrared Instrument as a low-resolution slitless spectrograph to observe four predicted transit windows for K2-22 b. For each observation, we extracted a transmission spectrum over the spectral range of 4.4–11.8 μ m. Over the spectral range of 4.4–8 μ m, where the spectral precision is highest, we detect one transit at high significance and two at low significance. While the signal-to-noise ratio of the spectrum limits our ability to draw firm conclusions, we find that the data (1) disfavor featureless, iron-dominated core material, (2) are consistent with some form of magnesium silicate minerals, likely from mantle material, and (3) show a distinct and unexpected feature at ∼5 μ m. The unexpected feature, also seen weakly in the low-significance transits, is consistent with an unknown gaseous absorber, possibly NO and/or CO _2 . These findings warrant further study to improve the constraints on the composition of this disintegrating rocky world.